Teaching drawing as a basis of imaging a creative idea - Morkytė, J. (Psichologija, 1962)
Perception and depiction in the creation of a realistic image are two sides of the same process that direct us towards a fuller understanding of the reality of the phenomenon. The unified management direction of these processes provides training and educational importance of drawing. The basics graphic drawing must be seriously taught in elementary school so that a small child’s arm muscles develop in this period of life, as well as forming accurate eye and hand coordination. The exact drawing development must be based on a physiological basis, psychological characteristics, and pedagogical training principles. a graphic skill mastery level when the child can more or less consciously express their thoughts and wishes drawing understandable forms is achieved gradually, when the child begins to look at his own drawing as a way of thinking and a way of communicating with others. This drawing takes on a social, increasingly more creative nature.